2023
DOI: 10.3389/fpsyg.2023.1069767
|View full text |Cite
|
Sign up to set email alerts
|

Perception of disease, dyadic coping, and the quality of life of oncology patients in the active treatment phase and their life partners: an approach based on the actor-partner interdependence model

Abstract: ObjectiveThe aim of this study based on the Systemic Transactional Model was to examine the relationship between dyadic coping and (1) disease perception and (2) quality of life of a sample of cancer patients and their life partners.MethodThis cross-sectional study included 138 oncological dyads. The following questionnaires were used: Stress Appraisal Measure, Dyadic Coping Inventory, and European Organisation for Research and Treatment of Cancer QLQ-C30. Data collected was analysed by applying the actor-part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
(82 reference statements)
0
3
0
Order By: Relevance
“… 24 ​Ştefănuţ et al. 25 highlighted that DC of oncology patients and their spouse caregivers has a significant influence on the couple's QoL and that positive DC provided by patients and reported by the caregivers had the effect of improving caregivers' QoL.…”
Section: Introductionmentioning
confidence: 99%
“… 24 ​Ştefănuţ et al. 25 highlighted that DC of oncology patients and their spouse caregivers has a significant influence on the couple's QoL and that positive DC provided by patients and reported by the caregivers had the effect of improving caregivers' QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that IP acts as a valuable psychological variable while attempting to improve the well-being of both CPs [ 23 ] and caregivers of patients with cancer [ 28 ]. Thus, to further improve the health and well-being of patients with CRC and SCs, health promoters should emphasize and utilize the mediating effects of IPs when providing psychological support [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“… 25 Research has shown that when couples work together, they can provide a supportive environment for each other, improve treatment outcomes and the quality of life. 26 A positive dyadic coping style can reduce emotional distress for both spouses, maintain good mental health and a stable relationship 27 , 28 . The negative dyadic coping style will reduce the disease adaptation ability of patients and spouses, which is not conducive to the regulation of their mental health.…”
Section: Introductionmentioning
confidence: 99%